Lumenal and Transmembrane Domains Play a Role in Sorting Type I Membrane Proteins on Endocytic Pathways - Reaves, Barbara J. (The American Society for Cell Biology, 1998)
Previous studies have shown that when the cytosolic domains of the type I membrane proteins TGN38 and lysosomal glycoprotein 120 (lgp120) are added to a variety of reporter molecules, the resultant chimeric molecules are localized to the trans-Golgi network (TGN) and to lysosomes, respectively. In the present study we expressed chimeric constructs of rat TGN38 and rat lgp120 in HeLa cells. We found that targeting information in the cytosolic domain of TGN38 could be overridden by the presence of the lumenal and transmembrane domains of lgp120. In contrast, the presence of the transmembrane and cytosolic domains of TGN38 was sufficient to deliver the lumenal domain of lgp120 to the trans-Golgi network. On the basis of steady-state localization of the various chimeras and antibody uptake experiments, we propose that there is a hierarchy of targeting information in each molecule contributing to sorting within the endocytic pathway. The lumenal and cytosolic domains of lgp120 contribute to sorting and delivery to lysosomes, whereas the transmembrane and cytosolic domains of TGN38 contribute to sorting and delivery to the trans-Golgi network.